1998
DOI: 10.1093/oxfordjournals.pcp.a029325
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Response Regulators from Arabidopsis thaliana Contain a Putative DNA-Binding Motif

Abstract: An expression sequence tag database of higher plants was screened by in silico profile analysis for response regulators of the two-component regulatory system. Two closely related clones (ARR1 and ARR2), corresponding to one of the extracted candidates, were isolated from Arabidopsis thaliana. The two genes were comparably expressed in all tissues, and at higher levels in the roots. The amino-terminal half of their translation products was highly conserved. This is where a phosphate receiver domain with the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 29 publications
4
71
0
2
Order By: Relevance
“…In other words, this B motif of ‫ف‬ 60 amino acids is a signature of the type-B family of ARRs. It also is related to plant GARP motifs, as emphasized in the Introduction (Riechmann et al, 2000), and its inferred consensus sequence shows similarity to the so-called plant Myb-related domains that are found in many plant proteins (Sakai et al, 1998). These include the well-characterized CCA1 (circadian clock-associated protein) and LHY (late elongated hypocotyl), both of which were classified as single Myb-related transcription factors of Arabidopsis (Schaffer et al, 1998;Wang and Tobin, 1998) (Figure 1A).…”
Section: Structure and Function Of The Type-b Family Of Arrsmentioning
confidence: 83%
“…In other words, this B motif of ‫ف‬ 60 amino acids is a signature of the type-B family of ARRs. It also is related to plant GARP motifs, as emphasized in the Introduction (Riechmann et al, 2000), and its inferred consensus sequence shows similarity to the so-called plant Myb-related domains that are found in many plant proteins (Sakai et al, 1998). These include the well-characterized CCA1 (circadian clock-associated protein) and LHY (late elongated hypocotyl), both of which were classified as single Myb-related transcription factors of Arabidopsis (Schaffer et al, 1998;Wang and Tobin, 1998) (Figure 1A).…”
Section: Structure and Function Of The Type-b Family Of Arrsmentioning
confidence: 83%
“…The type-A RRs are cytokinin primary response genes whose proteins consist mostly of a receiver domain with conserved D-D-K residues (Brandstatter and Kieber, 1998;Taniguchi et al, 1998;D'Agostino et al, 2000). The type-B RRs are more complex proteins that contain, in addition to the receiver domain, a DNA-binding motif (GARP domain) that resembles a domain originally found in the mammalian oncoprotein c-Myb (Imamura et al, 1998;Sakai et al, 1998). While phosphorylated type-B RRs act as transcriptional activators of cytokinin-regulated genes, the type-A RRs down-regulate cytokinin signaling by competing with the type-B RRs for phosphoryl groups (for review, see To and Kieber, 2008).…”
mentioning
confidence: 99%
“…The mammalian Myb generally consists of three repeats, each of which contains three distinctive modules that respectively center on a tryptophan residue (Ogata et al, 1992). In contrast, ARRM contains one repeat, and the conserved tryptophan residues in the second and third modules are replaced by either alanine or isoleucine residues in the cases of ARR1 and ARR2 (Sakai et al, 1998). ARRM binds double-stranded DNA in a sequence-specific manner in vitro , although initially this characteristic was in doubt, since ARRM has lowlevel homology to Myb.…”
Section: Structure and Biochemical Characteristics Of The Arabidopsismentioning
confidence: 99%
“…We found that a considerable number of response regulator genes were distributed among the plant genomes. Furthermore, these loci encoded proteins that could be classified into two groups: the A-type proteins were relatively small molecules that seemed to consist of only a signal receiver domain and an extremely short stretch at the C-terminus, whereas the B-type proteins contained additional functional domains after the signal receiver domain (Imamura et al, 1998;Sakai et al, 1998). Since the entire Arabidopsis genome sequence is now available (The Arabidopsis Genome Initiative, 2000), we know that Arabidopsis carries eleven genes for each of the A-type and B-type response regulators ( ARR1 to ARR22 ), eleven sensor histidine kinase genes ( AHK ), and five HPt protein genes ( AHP1 to AHP5 ).…”
Section: Introductionmentioning
confidence: 99%